Patency of Peripheral Venous Catheter: An Observational Study - H.N. , Ravindra; Patil, Sunaina; Patel, Sonal; Rahane, Swapnil (International Journal of Psychosocial Rehabilitation, 2020)
Background: During the hospitalization period of patients, a PVC is a frequently used device to administer medication or intravenous fluids. PVC is a plastic catheter that is directly placed into veins. If proper care is not taken, the risk of acquiring systemic blood infections and local infections is increased, as it is a foreign body. Such infections can lead to life-threatening complications.Aim: To assess patency of PVC was the aim of the study.Materials and Method: A quantitative study with a descriptive research design was carried out to assess the patency of PVC. With the use of the systematic random sampling technique, 270 inpatients of a tertiary care hospital were selected. To survey factors related to PVC, the modified VIP scoring scale was used. Recurrence rate of demographic variables was analyzed by descriptive statistics. Collected information was associated with demographic variables with the use of SPSS software.Results: Collected data stated that the dominant part of male inpatients (75%) were in the age group of 29-30 years; patients admitted to the general ward and having acute illness were 64% (174). Additionally, the study uncovered that the frequency of non-patent catheters was 54.44% (147), which was high and noteworthy affiliation was found with the length of intravenous catheterization at a significance level of 0.05.Conclusion: From the above discoveries, it is clear that the maximum number of catheters discovered were non-patent and were related to long periods of insertion of PVC. Henceforth it is suggested potential complexity can be diminished with standard procedural rules and skillful nursing practice.